The complete plastome genome and its inference on the phylogenetic position of Bletilla formosana (Orchidaceae) - Wu, Xiayu (Mitochondrial DNA B Resour, 2019)
Bletilla formosana is a traditional Chinese medicinal herb and recently threatened by overexploitation owing to the increasing demand. In present study, we sequenced and assembled the complete chloroplast (cp) genomes of this species. The plastome genome is a typical quadripartite circle molecule with the total lenth of 158,968 bp and overall GC content of 37.3%. We predicted 104 genes in the cp genome, including 80 protein coding gens, 20 tRNA and 4 rRNA. Phylogenetic analysis shows that B. formosana is sister to B. striata.